(untitled) (Progressive Agriculture, 2013)
This study was conducted to evaluate the quality changes in an important crustacean species giant freshwater prawn, Macrobrachium rosenbergii (locally called golda) at various stages of handling. The samples under study were obtained from farms and depots of four golda producing districts viz. Khulna, Bagerhat, Jessore and Norial area by determining organoleptic and biochemical aspects. The golda samples stored in ice immediately after harvest were in acceptable condition for seven days after harvesting period while the samples obtained from depots from all stations were in acceptable condition for 4 days only. There was a large fall of protein solubility and ATPase activity in all the samples obtained from farms and depots. The fall of solubility and ATPase activity was faster in samples obtained from depots compared to the samples obtained from farm immediately after harvest. The large fall of protein solubility and ATPase activity of samples indicated the denaturation of protein during ice storage. DOI: http://dx.doi.org/10.3329/pa.v22i1-2.16476 Progress. Agric. 22(1 & 2): 139-149, 2011